2015
DOI: 10.1002/etc.2890
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of the conventional energetics TNT and RDX relative to new insensitive munitions constituents DNAN and NTO in Rana pipiens tadpoles

Abstract: An initiative within the US military is targeting the replacement of traditional munitions constituents with insensitive munitions to reduce risk of accidental detonation. The purpose of the present study was to comparatively assess toxicity of the traditional munitions constituents 2,4,6-trinitrotoluene (TNT) and 1,3,5-trinitroperhydro-1,3,5-triazine (RDX) with the new insensitive munitions constituents 2,4-dinitroanisole (DNAN) and 3-nitro-1,2,4-triazol-5-one (NTO). The following exposure durations were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…However, mortality occurred at much lower concentrations when exposures were extended to 90 days, with the lowest-observable-effect concentration (LOEC) values ranging from 0.12 to 0.21 mg/L (Figure 66) . For tadpoles of the leopard frog (R. pipiens), the 4-day LC50 for TNT (4.4 mg/L) was similar to that for the African clawed frog and similar to those observed by Paden et al, which extended the exposure, in this case, to 28 d and dramatically decreased the effects concentration (LOEC = 0.003 mg/L) (Stanley et al 2015). Tadpoles of the leopard frog were more tolerant to RDX than TNT during 10-and 28-day exposures (Stanley et al 2015).…”
Section: Toxicity Of MC To Aquatic Larval Stages Of Amphibianssupporting
confidence: 84%
See 1 more Smart Citation
“…However, mortality occurred at much lower concentrations when exposures were extended to 90 days, with the lowest-observable-effect concentration (LOEC) values ranging from 0.12 to 0.21 mg/L (Figure 66) . For tadpoles of the leopard frog (R. pipiens), the 4-day LC50 for TNT (4.4 mg/L) was similar to that for the African clawed frog and similar to those observed by Paden et al, which extended the exposure, in this case, to 28 d and dramatically decreased the effects concentration (LOEC = 0.003 mg/L) (Stanley et al 2015). Tadpoles of the leopard frog were more tolerant to RDX than TNT during 10-and 28-day exposures (Stanley et al 2015).…”
Section: Toxicity Of MC To Aquatic Larval Stages Of Amphibianssupporting
confidence: 84%
“…In addition, a chronic WQC value for TNT was calculated using a revised acute-chronic ratio that included new studies. The new studies show that two tadpole species (R. pipiens and R. catesbeiana) have a much higher chronic sensitivity to TNT Stanley et al 2015).…”
Section: Toxicity Of MC To Aquatic Invertebrates and Fish In Sedimentmentioning
confidence: 80%
“…NTO is highly soluble (16,642.0 mg L À1 at 25 C) (Spear et al, 1989) and its transport to groundwater used as potable water source could result in human exposure to the chemical. While NTO showed low toxicity to the freshwater organism Ceriodaphnia dubia, green algae Selenastrum capricornutum (Haley et al, 2009), and Rana pipiens tadpoles (Stanley et al, 2015), it is a male reproductive toxicant in rats (Wallace, 2011;Lent et al, 2015) and was reported to form transformation products that can be toxic if they behave similarly to metabolic intermediates of other nitro-compounds (Le Campion et al, 1999b). Based on these risks, accurate soil adsorption coefficients (K d s) and transformation rate constants are necessary to simulate and predict NTO fate and transport to groundwater.…”
Section: Introductionmentioning
confidence: 96%
“…Both DNAN and its transformation products exhibit microbial toxicity (with amino products being less toxic than DNAN) ; as well as toxicity to higher organisms (Dodard et al, 2013). However, DNAN toxicity is comparable to or less than that of TNT (Dodard et al, 2013;Stanley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%